Galfenol Nanowires for Touch Sensors and Electroplated Thin Films - Kuehn, Katherine A. (My University, 2011)
The goal of this project was to electroplate and characterize thin films of metal alloys that have not been previously studied. All of the desired thin films were able to be electroplated, but the compositions of the films were not ideal. Once perfected, these alloys will be used to grow nanowires to develop touch sensors.
Color poster with text, images, diagrams, and graphs.
Keywords: Nanostructured materials; Nanotechnology--Research; Sensor networks; Thin films--Testing; Posters